Intercultural interpretation discourses, techniques and strategies used by tour guides in the Coach Museum, Lisbon : Eight issues - Brito, Luís Miguel (Institute of Foreign Languages and Communication of the Budapest Business School, 2017)
The Coach Museum in Lisbon houses one of the finest collections of coaches in the world. It is the second most visited museum in Portugal and it is often included in the Lisbon city tour. Tourist guides often perform visits to the museum. They are mediators between heritage and tourists, involving them not only in the collection but also in the life of the people who used the coaches. A guided tour to the museum can be either a nightmare or nice dream. It will be a nightmare if the guide conveys uninteresting information about the objects and vehicles exhibited, if s/he is centred on him/herself. But it can also be very lively and interesting if interpretation strategies are centred around the tourist and his/her culture. The aim of intercultural interpretation is to awaken different kinds of emotions in the tourist, from piety to amusement, using fantasy and reality. This paper discusses the different characteristics tourist guides’ interpretation assumes in Lisbon’s Coach Museum. The researcher heard the speech of fifty professional guides visiting the museum, during the months of September and October 2009. Data obtained were included in his PhD thesis. The anthropological technique applied is direct observation, defined as “direct involvement of the field researcher with the social group studied, within the parameters of the group standards” (Iturra, 1987: 149). The paper is divided into the following parts: introduction (including tourist information versus intercultural heritage interpretation, methodology, interpretation- eight issues, and final considerations. The observation of tourist guides in their working context allowed the identification of the intercultural skills developed by these professionals, the interpretative strategies adopted in communication, and some behavioural patterns of both guides and tourists.
Keywords: Intercultural interpretation; Interpretação Intercultural; Tourist guides; Guias intérprete; Coach Museum; Museu dos Coches; Lisbon; Lisboa